Peran Tu’a Golo Dalam Konteks Perubahan Sosial (Studi Etnografisgendang Di Kecamatan Langke Rembong, Kabupaten Manggarai Provinsi Nusa Tenggara Timur) - Keristian Dahurandi (STIPAS St. Sirilus Ruteng, 2018)
Tu’a golo is the name for the head of beo/gendang (kampong, corresponds to the traditional rural community) within the cultural setting of Manggaraian society, in the East Nusa Tenggara Province. Basically, the main role of tu’a golo is closely related to the traditional system of governance of Manggaraian society which includes: first, mbaru bate kaeng (house of residence), second, uma bate duat (place of work), third, natas bate labar (village yard for socializing and creativity), fourth, wae bate teku (water springs for life), fifth, compang (altar offerings). In the context of Gendang in the District of Langke Rembong, the role of tu’a golo is shifting due to several things: first, the diversity of single activity of the house to plurality of social activities offered by various social institutions; secondly, there is limited space (lingko) to be able to carry out the role of lodok lingko (distribution of land) so that tu’a golo only acts as a witness concerning the boundaries of the ownership of the land when the issue of positive law arises; third, the paradigm shift of thinking of the people because of the development of science and technology which tends to revise the traditional way or cultural approach that is considered traditional.